The experience economy - Pine, B. Joseph (Harvard Business Review Press, 2011)
Welcome to the new Experience Economy. With this fully updated edition of the book, Pine and Gilmore make an even stronger case that experience is the missing link between a company and its potential audience. It offers new rich examples—including the U.S. Army, Heineken Experience, Autostadt, Vinopolis, American Girl Place, and others—to show fresh approaches to scripting and staging compelling experiences, while staying true to the very real economic